E-Consumer Privacy Policy on the Online Marketplace System - khitam, Muhammad chusnul; Suisno; Nugroho, Fajar Seto; Rizkiyah, Putri Ainiyatur (Universitas Islam Lamongan, 2024)
Abstract How should the protection of privacy and personal data in Indonesia be responsive to anticipate changing trends from the traditional economic era to the digital economic era? Rapidly developing information and communication technology is changing the way people run business and/or carry out transactions. Thus, transactions which are known as